ANALISIS KESULITAN SISWA BERDASARKAN GENDER DALAM MENYELESAIKAN PERMASALAHAN MATEMATIS - Marselina Ina; Timbul Yuwono; Tatik Retno Murniasih (Universitas Insan Budi Utomo, 2024)
The aim of this research is to analyze the mathematical problem solving abilities of class VIII middle school students based on the student's gender. This research is a qualitative descriptive study. The subjects in this research were 23 students in class VIII of Malang National Middle School, consisting of 11 male students and 12 female students. Then 6 subjects were selected, namely 3 men and 3 women who had mathematical problem solving abilities in the high, medium and low categories. The research was carried out in the second semester of the 2022/2023 academic year. Analysis was carried out by giving a written test in the form of 2 essay questions. The material tested is problem solving questions related to the Pythagorean theorem. The results of the analysis of students' problem solving abilities were obtained based on the results of student work and interviews. The results of this study indicate that female students' mathematical problem solving abilities are better than male students in solving problems related to the Pythagorean theorem.